The impact of organisational culture on attitudes concerning change in post-soviet organisations - Ruth Alas; Maaja Vadi (Journal for East European Management Studies, 2004)
906 employees from Estonian companies were studied in order to explore how task-orientation and relationship-orientation of organisational culture influence attitudes to the process of organisational change among employees in post-socialist organisations. The current survey indicates that people who began working in the former Soviet Union differ from those who started their careers during the subsequent transition period according to the way they form their attitudes toward change. Relationship-orientation of organisational culture predicts a belief in the benefits of change only in the group of people who started their work life in Soviet organisations. – – In einer Studie wurden 906 estnische Mitarbeiter von Firmen studiert um zu untersuchen, wie die Aufgabenorientierung und Beziehungsorientierung in der Organisationskultur die Einstellungen von Angestellten zum Prozess von organisatorischen Veränderungen in post-sozialistischen Organisationen beeinflusst. Die neueste Studie zeigt einen Unterschied hinsichtlich der Einstellung zu Veränderungen zwischen jenen die in der früheren Sowjetunion zu arbeiten begannen und jenen die ihre Karriere in den darauf folgenden Jahren des Übergangs starteten. Die Beziehungsorientierung in einer Organisationskultur sagt nur einen Glauben an Vorteile von Veränderungen in der Gruppe von Menschen voraus, die ihr Arbeitsleben in sowjetischen Organisationen begannen
Keywords: 650; Organizational change; organizational culture; employees' attitudes toward changes; post-soviet organization